Characterization and shelf life testing of bigscale goatfish (Pseudopenaeus grandisquamis) tocino produced in Cadiz City, Negros Occidental - Lao-as, Kristen Anne Villa (2011.)
Unpacked and packed bigscale goatfish tocino produced in Cadiz City, negros Occidental was characterized in terms of its physico-chemical properties (MC, aw, pH, TSS, salt content, TVB-N and TMA contents).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Goatfish; Pseudopenaeus grandisquamis; Tocino